2007
DOI: 10.1577/m06-147.1
|View full text |Cite
|
Sign up to set email alerts
|

Sampling a Littoral Fish Assemblage: Comparison of Small‐Mesh Fyke Netting and Boat Electrofishing

Abstract: We compared small‐mesh (4‐mm) fyke netting and boat electrofishing for sampling a littoral fish assemblage in Muskegon Lake, Michigan. We hypothesized that fyke netting selects for small‐bodied fishes and electrofishing selects for large‐bodied fishes. Three sites were sampled during May (2004 and 2005), July (2005 only), and September (2004 and 2005). We found that the species composition of captured fish differed considerably between fyke netting and electrofishing based on nonmetric multidimensional scaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 28 publications
11
116
0
Order By: Relevance
“…1). We deployed three smallmesh fyke nets (described in Ruetz et al 2007) and two minnow traps at each site. Gears were deployed between 9:00 and 11:30 a.m. the previous day to allow the gears to fish for about 24.6 h. All the fish captured were identified and measured (total length) to the nearest 1 mm.…”
Section: Tributariesmentioning
confidence: 99%
“…1). We deployed three smallmesh fyke nets (described in Ruetz et al 2007) and two minnow traps at each site. Gears were deployed between 9:00 and 11:30 a.m. the previous day to allow the gears to fish for about 24.6 h. All the fish captured were identified and measured (total length) to the nearest 1 mm.…”
Section: Tributariesmentioning
confidence: 99%
“…Rather, Fago (1998) obtained a more accurate estimate of species composition by combining the results from both methods. Likewise, Ruetz et al (2007), when testing boat electrofishing strategies against fyke nets, concluded that multiple gear types should be used in monitoring surveys of fish assemblages. Similar results are described by Jackson and Harvey (1997) using different types of traps and gill nets in lakes.…”
Section: Practical Advicementioning
confidence: 99%
“…We used round goby densities of 5-15 individuals/m 2 in enclosures, which are not uncommon in the Great Lakes (Ray and Corkum 2001;Barton et al 2005;Johnson et al 2005) with densities as high as 133 individuals/m 2 reported in areas of Lake Michigan (Chotkowski and Marsden 1999). However, the size and density of round gobies in cages were likely greater than round gobies inhabiting littoral habitats in Muskegon Lake given the size and number of round gobies collected in fyke nets (Cooper et al 2007(Cooper et al , 2009Ruetz et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that habitat type is critical for predicting the effect of round goby predation on Dreissena density. For example, in areas of SAV in coastal lakes of eastern Lake Michigan, round goby are not likely to strongly reduce Dreissena densities because of the size structure of round gobies (i.e., more small individuals) and round gobies are likely consuming energy rich non-mussel invertebrates rather than Dreissena as their dominant food source (Cooper et al 2007(Cooper et al , 2009Ruetz et al 2007Ruetz et al , 2009). Our hypothesis should apply beyond eastern Lake Michigan and should be tested in other areas in North America and Europe where the round goby is invading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation